Innovations in publishing technologies: Enhancing reader experience - Kalmykov , Alexey (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
In this research, the effects that digitalization has had on existing publishing workflows in the context of content creation, circulation and monetization are explored. The emergence of digital platforms, self-publishing, and subscription-based services junked the old ways of publishing content; how is it authored, disseminated and consumed and the current trends suggest multiple impacts on various segments of the digital advertising. However, digital has opened up the door for audiences to enjoy more interactive, and personalized experiences which has led to rapid growth in eBooks, audiobooks and digital subscriptions. But in doing so, it’s given publishers a host of challenges: how to enforce copyrights, combating the dominance of the Amazon kind of platform, and finding viable ways to monetize sustainably.The main aim of this study is to evaluate the benefits and drawbacks of digitalization for publishers, in terms of technological integration and its effects of the publishing process. The research explores the impact of digital tools, including Augmented reality, Artificial intelligence, and blockchain, on the industry, and the hurdles that publishers have in adopting these innovations. Additionally, the study describes how publishers are changing their business models and content strategies to respond to the changing audience needs